Validity of a novel device for real-time analysis of cyclists` drag area - Valenzuela, P. L.; Alcalde, Y.; Gil-Cabrera, J.; Talavera, E.; Lucia, A.; Barranco-Gil, D. (Journal of Science and Medicine in Sport, 2020)
Objectives: To assess the reliability, validity, and sensitivity of a novel device (Notio Konect™) which is purported to provide a real-time analysis of aerodynamic drag area (CdA) during cycling. Design: Observational, cross-sectional study. Methods: Fifteen trained cyclists rode in an indoor velodrome using three different positions (upright, aero [holding aero bars], and optimized aero [similar to aero, but wearing a time-trial helmet]). They completed six 1-min trials in each position. The CdA was measured with Notio and with two other systems (Track Aero System™ [TAS] and a validated mathematical model). Results: The CdA measured with Notio showed good reliability (intra-class correlation coefficient [ICC] = 0.92, 90% confidence interval [CI] = 0.89-0.95). Notio showed an almost perfect relationship with both TAS (ICC = 0.99, 90% CI = 0.98-0.99) and the mathematical model (ICC = 0.99, 90% CI = 0.98-0.99). However, the CdA values provided by the former (0.308 ± 0.051 m2) were significantly higher (albeit with a trivial effect size [ES]) compared with TAS (0.300 ± 0.051 m2, p < 0.001, ES = 0.15) and the mathematical model (0.303 ± 0.051 m2, p = 0.005, ES = 0.09). The CdA was higher in the upright than in the aero position with all systems (all p < 0.001, ES = 1.84-1.89), and higher in the aero than in the optimized aero position when measured with TAS (p = 0.033, ES = 0.22) or the mathematical model (p = 0.024, ES = 0.24), but not with Notio (p = 0.220, ES = 0.19). Conclusions: Notio appears to be reliable, strongly correlated to other established systems, and discerns large (upright vs aero) but not small (aero vs optimized aero) variations in riding position. Further research is needed to confirm its validity in outdoor conditions.